PENINGKATAN NILAI NUTRISI LIMBAH LUMPUR MINYAK SAWIT SEBAGAI PAKAN TERNAK - Sindu Akhadiarto (Jurnal Rekayasa Lingkungan)
Indonesia is the largest country that has oil palm plantations, covering 7.3 million ha area (2009), with production of 19.4 million tonnes of crude palm oil (CPO) which is expected to palm oil sludge waste as much as 1.94 million tons/year. Palm oil sludge waste is one alternative to potential animal feed ingredients. The low nutritional value and high fiber content causes palm oil sludge requires special treatment before given to animal. The fermentation process is able to increase the nutritional value of the palm oil sludge, such as increasing levels of crude protein and energy metabolism, and also may reducing content of coarse fiber. This fermentation product can be stored at room temperature for 12 weeks without experiencing significant changes in nutritional value. The usage limit of palm oil sludge which is recommended for poultry is 15%. The optimum limit of palm oil sludge in the diets of goats and sheep is 47% and 40% for cows (in concentrate). The use of rice bran on ruminants can be replace entirely by the palm oil sludge. Fermentation techniques can be done to improve the nutritional value of the palm oil sludge, but this technique needs to be studied economically, such as: during the drying process (because of the high content of LMS), and the quite expensive fermentation. Another technique to minimize costs has been done, for example by utilizing the available energy sources in the plant oil.Keywords: palm oil sludge, nutritive values, ruminant, poultry, fermentation.